Medical appointment application - Ismail, Noorsyahira; Kasim, Shahreen; Jusoh, Yusmadi Yah; Hassan, Rohayanti; Alyani, Ayu (2018)
The current standard operating procedure in healthcare environment for patient registration and appointment scheduling are time consuming and somehow troublesome. Medical Appointment Application is a web-based mobile application develop for managing appointment-booking process for a few medical organizations, regardless of the type of service they schedule in Parit Raja and Batu Pahat area. The practices will have to sign up on the online appointments portal themselves and can view the appointment made by user, the patients. It will help user, the patients to book their appointment using the Medical Appointment application. Furthermore, Prototype Model is used to develop this system. As for the hardware and software used to develop this system is MySQL Database and programming language use is PHP and JavaScript. By developing this system, it will reduce the number of calls for an appointment and avoid the morning rush for an urgent appointment. Also, it will potentially reduce the need for extra reception staff, a significant reduction in labor. Furthermore, it helps user in time saving and avoiding the need to negotiate with the receptionist for a convenient appointment time. This technology can transform the current daunting appointment process and enable them to run more efficiently, effectively and profitably.